The Effect of the 2010 Thai Political Crisis on the Stock Exchange of Thailand - Vanaratnachai, Krittaya (2010)
This study examines the relationship between political events that occurred in an emerging stock market, Thailand, and stock returns during the first half of 2010. The political movements observed are riots, violence clashes, protesting and destruction that took place between February and May 2010, 8 events have been examined. Event study methodology has been used to observe the abnormal and cumulative returns throughout the event window. A classical event study methodology was applied to test the relationship. The technique was adapted from Brown and Warner (1980, 1985) and Seiler (2004) by means of the market model. This methodology allows us to examine the impact of the recent Thai political crisis by deviation of index returns from their average. Further to this, a sectorial effect analysis was conducted on each sector listed on the Stock Exchange of Thailand (SET) to investigate the impact of the political crisis on those sectors. The empirical results indicate that the Thai stock market is efficient at semi strong form, to a certain extent and the market reacts to political events. Although some events did not dramatically affect the market, most of the events tested shows that massive and unexpected incidents cause the most shock on the stock market. Results show that some industries are more affected from political activities. Out of these sectors, banking, property development, automotive and agribusiness were mostly affected from the political unrest. The SET did experience plunges during significant incidents but did not crash because investors, local and foreign, had confidence that the country will regain its tranquility. This finding also correlates with other studies conducted on SET to establish if the market is efficient at the semi strong form. Since not events all impacted the SET, investors can observe the behavior of the returns and regulators can implement policy for future mishaps. Certain political events cannot always be predicted and avoided. However, in the era of Information and Communication Technology (ICT), sharing of real time information amongst market participants and regulators means that they have quicker access to market data. Hence more efficient backup and recovery strategies can be applied. A distinct conclusion cannot be drawn since the political crisis is ongoing and for the purpose of this research a short time frame was observed.